Chain rigidity modification to promote the electrochemical performance of polymeric battery electrode materials. Issue 17 (9th April 2019) - Niu, Zhihui; Wu, Huaxi; Liu, Lei; Dai, Gaole; Xiong, Shiyun; Zhao, Yu; Zhang, Xiaohong
Abstract : Tuning the chain rigidity enables high power density without sacrificing the volumetric energy density for polymeric battery materials. Abstract : Redox-active polymers are promising materials for rechargeable batteries because of their structural diversity and resource sustainability. We present in this work the feasibility of manipulation of the rigidity of polymer chains to alter the ion diffusion behaviour in polymeric materials. The results indicate that the ionic diffusion coefficient is enhanced by orders of magnitude if a proper twisted group is introduced to interrupt the rigid backbone of the polymers. Both greater galvanometric and volumetric power/energy densities have been achieved for the polymer with more flexible chains, regardless of its lower surface area and electrical conductivity compared to the one with a more rigid chain structure. Such a strategy might be useful for the design of polymeric battery materials with high power density without sacrificing the volumetric energy density.